Does education indoctrinate?. (October 2020) - Diwan, Ishac; Vartanova, Irina
Highlights: We measure lower and upper bounds of the differential effect of education in democracy and autocracy on political beliefs and behaviors, taking into account possible biases related to fear of state sanctions and/or reverse causality. Using World Value Survey data, we find that the political values held by individuals that were educated under an autocratic regime but live in a democracy are more conservative than those held by individuals that were both educated and live in a democracy. The effect of education on political values is found to be on average relatively small, but the differences across political regimes of these effects are large, and highly significant. For individuals educated in a democracy, the political return to higher education in terms of the value Respect for Authority is estimated to be 0.70 to 0.77 times lower (or between 0.06 and 0.18 standard deviations) than for those educated under autocracy. Higher education increases Civic Action for individuals educated under a democratic regime by between 27 percent and 65 percent more than for individuals educated under an autocratic regime (which represent respectively 0.18 and 0.59 standard deviations). For voting, the return to education is 45 % lower for university students in autocracies relative to democracies. Abstract: Do states manage to build education systems that produce students with political values they uphold? We test the indoctrination hypothesis using World Value Survey data spanning 96 countries. We devise an empirical strategy that can identify the effects of education on political values by using information about the political regime under which individuals live, and regimes under which they got educated. Our results suggest that state indoctrination is at work. For example, we find that higher education increases voting behavior by at least 45 percent more for cohorts that have studied in a democratic rather than an autocratic country.